2000
DOI: 10.1063/1.481727
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic disorder of azulene: A single crystal deuterium nuclear magnetic resonance study

Abstract: Deuterium nuclear magnetic resonance measurements on single crystals of azulene, specifically deuterated in the 1 and 3 positions, are reported. The quadrupole coupling tensor of these deuterons was determined by rotation experiments, yielding Qzz=182.2 kHz and η=0.056, with Qxx, the intermediate component (magnitude wise), oriented perpendicular to the molecular plane. The deuterium signals are inhomogeneously broadened and their widths are strongly anisotropic. This is quantitatively interpreted in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The derived correlation times and the activation energy for the ring flip motion fall within the typical range which is discussed for solids with phenyl rings that undergo rotational motion around a C-C single bond (polymers, 22,64,65 proteins, molecular crystals, etc.). [66][67][68][69][70][71][72][73] For instance, 13 C NMR studies were performed on poly(p-phenylene vinylene) (PPV) films, which have shown that the phenyl rings in both the amorphous and crystalline regions undergo 1801-ring flips with activation energies ranging from 20 to 60 kJ mol À1 . 59,73 It is interesting to note that in inclusion compounds also other intramolecular processes, like methyl group rotation, ring inversion or conformational changes, have been examined which again were found to remain almost unaffected by the surrounding host lattice.…”
Section: Resultsmentioning
confidence: 99%
“…The derived correlation times and the activation energy for the ring flip motion fall within the typical range which is discussed for solids with phenyl rings that undergo rotational motion around a C-C single bond (polymers, 22,64,65 proteins, molecular crystals, etc.). [66][67][68][69][70][71][72][73] For instance, 13 C NMR studies were performed on poly(p-phenylene vinylene) (PPV) films, which have shown that the phenyl rings in both the amorphous and crystalline regions undergo 1801-ring flips with activation energies ranging from 20 to 60 kJ mol À1 . 59,73 It is interesting to note that in inclusion compounds also other intramolecular processes, like methyl group rotation, ring inversion or conformational changes, have been examined which again were found to remain almost unaffected by the surrounding host lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the orientation dependence of 2 H NMR spectra have been successfully applied for the study of crystalline substances, but are equally suitable for the measurement of residual anisotropies of the pseudonematic effect in polymers and ionomers. , In such experiments, the sample is mounted in a goniometer, allowing for measurements of 2 H NMR spectra at different relative orientations to the magnetic field B 0 . These orientations are varied through rotating the sample by defined angles ϕ.…”
Section: Methodsmentioning
confidence: 99%
“…We further suggest a herringbone structure for 18, based on its parent azulene. 99,100 To the best of our knowledge, none of the molecules we propose have been synthesized; however, molecules with related structures have been reported. Introducing two BN units into a benzene ring has been achieved (see ref 53 and the references therein).…”
Section: ■ Some Further Considerationsmentioning
confidence: 99%